Legal Certainty for Mothers in Child Custody Disputes: Implications of Deficiency of Child Custody in the Indonesian Legal System - Wirotomo, Heristiawan Aryo; Somala, Taufik Dany; Nuha, Royus Yunior Stivenson; Suistiyono, Dwi Setiaputra; Astuti, Sri Ayu (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the impact of confiscation of custody rights for mothers and children and its implications for the Indonesian legal system, in order to formulate an ideal legal settlement for child custody disputes in the future so that justice is achieved for the mother. This study uses a normative juridical research method using statute approach and case approach. The research resulted that it was found the impact of the confiscation of child custody rights not only affects the psychological condition of the mother and child, but also creates uncertainty in the justice system in Indonesia. The confiscation of custody rights by ex-husbands shows weaknesses in law enforcement and a lack of adequate protection for mothers and children.